Rethinking How to Teach Programming to Newcomers. - Robertson, Judy (Communications of the ACM, 2014)
The author discusses her efforts to introduce the development of applications for the Android mobile device operating system into her introductory university-level computer programming course. Topics include the challenge of implementing a curriculum to match the varying levels of experience among first-year students, the use of the App Inventor visual programming platform and the Eclipse Android development system, and student reactions to the software including comments on its ease of use and its limitations.